Spatio -temporal Analysis Of Maternal Mortality In Jigawa State, Nigeria - Muhammad, Abdulkadir (2021)
Maternal mortality is still a major risk for women of childbearing age in Nigeria. Nigeria bore 14% of the global burden of maternal mortality. The national maternal mortality ratio has remained elevated despite efforts to reduce maternal mortality. Though health disparities exist between the North and South of Nigeria, there is a dearth of evidence on the estimates and determinants of maternal mortality for these regions The trend of Maternal Mortality case increases every year in Nigeria. especially in Jigawa State, based on the latest report and survey from National Demographic health survey (NDHS, 2018), and Multiple Cluster Indicator Survey placed the state as state with high burden of disease profile and Maternal Mortality ratio of the state as very high and is still unsatisfactory. Therefore, this study was conducted to identify trends of Maternal Mortality, spatial pattern and modelling the causes of Maternal mortality in Jigawa state, Nigeria. Maternal Mortality data for Ten years (2008 to 2017) was obtained from Jigawa state Ministry of Health, statists Unit.